Developing Industry or a Sector without a Future? Modernization of the Baltic Fisheries of the Polish People’s Republic in the Years 1970–1989 and its Impact on the Local Community of the Hel Peninsula - Kubicki, Mateusz (Vade Nobiscum, tom XXIII/2021: Studia nad XIX i XX wiekiem, 2021)
The article aims to present the influence of the state, Baltic fishing on the community of the Hel Peninsula. The first part discusses the geographic and biological aspects of the spit and the history of the state-owned fisheries in the Baltic Sea, including the described area. The second part indicates the issues related to the crystallization of individual entities on the Hel Peninsula and the stages of modernization of state-owned enterprises and cooperatives until 1989. The last part of the article presents the impact of fishing on the local community, indicating both positive and negative aspects. The privatization fate of entities and the impact of the restructuring process on people living on the Hel Peninsula are supplementary.